2019
DOI: 10.1039/c8cp06600k
|View full text |Cite
|
Sign up to set email alerts
|

Conformational isomerism controls collective flexibility in metal–organic framework DUT-8(Ni)

Abstract: The linker orientation in conformational isomers of DUT-8(Ni) determines the flexibility of this metal–organic framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
78
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 47 publications
(86 citation statements)
references
References 45 publications
7
78
0
1
Order By: Relevance
“…The comparison of this value with corresponding M -N bond lengths in and, shows that the value in DUT-8(Zn) is in between. The Zn-Zn-N angle is 178.65°, and comparable with that observed in DUT-8(Ni) (177.59°) (Table S1, ESI) 56. Particle sizeAs we have reported for DUT-8(Ni) and DUT-8(Co), the switching characteristics are sensitive to crystal size distribution and it was also expected for DUT-8(Zn).…”
supporting
confidence: 85%
See 1 more Smart Citation
“…The comparison of this value with corresponding M -N bond lengths in and, shows that the value in DUT-8(Zn) is in between. The Zn-Zn-N angle is 178.65°, and comparable with that observed in DUT-8(Ni) (177.59°) (Table S1, ESI) 56. Particle sizeAs we have reported for DUT-8(Ni) and DUT-8(Co), the switching characteristics are sensitive to crystal size distribution and it was also expected for DUT-8(Zn).…”
supporting
confidence: 85%
“…Crystal-downsizing was accomplished by supersaturation route, reported by Kavoosi et al in 2017 for the synthesis of rigid DUT-8(Ni) 56. All chemicals were dissolved separately: Zn(NO3)2•6H2O (446 mg, 1.5 mmol, 0.5 eq.)…”
mentioning
confidence: 99%
“…All simulations were carried out using GROMACS 5.1 41 with PLUMED 2.2 51 . In the case of isolated half-SBUs in solution, we investigate the structural flexibility of all three isomers as conformational isomerism is found to regulate the flexibility of the resulting framework 52 . In this context, we sample their conformational space performing WTmetaD 46 simulations using the massweighted radius of gyration (Rgyr) as a collective variable (CV).…”
Section: Methodsmentioning
confidence: 99%
“…A porous coordination polymer [Zn 2 (bdc) 2 (dabco)] (dabco = 1,4-diazabicyclo [2.2.2]octane) is a prototypic compound of a bountiful MOF family with highly tunable structural features [26][27][28][29][30]. We have demonstrated that the incorporation of 2,5-thiophenedicarboxylate instead of the 1,4-benzenedicarboxylate into this MOF enhances both the CO 2 adsorption uptake and the CO 2 /N 2 adsorption selectivity of [Zn 2 (tdc) 2 (dabco)] by as much as 50%, compared with the original structure [Zn 2 (bdc) 2 (dabco)] at the same conditions [31].…”
Section: Introductionmentioning
confidence: 99%